Comparative study of operative management of humeral shaft fractures by dynamic compression plating versus locked intra-medullary nailing - Koppolu Kanthi, Kiran Kumar; Lakkireddy, Maheshwar; Bollavaram, Vikas Reddy; Rapur, Siva Prasad (International Journal of Research in Orthopaedics, 2017)
Background: Operative management of humeral shaft fractures is mostly accomplished by surface plating or intra-medullary nail osteosynthesis. Both the treatment options have been variably reported to give good rates of union and functional outcome. We compared both the options to know the better one in multitude of variables. Methods: Thirty patients with fracture shaft of humerus were followed up for a period of 12 to18 months. 15 patients each underwent open reduction and internal fixation with dynamic compression plate and closed antegrade locked intra-medullary nailing. All patients were clinically and radiologically assessed till fracture union. Results: Diaphyseal humeral fractures in all the patients treated with nailing united and had a tendency to unite early compared to plating. Shoulder pain was initially complained by 2 patients from the nailing group and got subsided later on. The incidence of complications was more in the plate osteosynthesis group. Conclusions: In our study Intra-medullary nailing turned out to be superior to plating for amenable diaphyseal fractures of humerus in terms of higher rate of union, early union and lesser complications.